Multi-Ethnic Communities and Religion: How Responsive are Irish Primary Schools to Cultural and Religious Diversity? - Foley, Aron (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Sociology, 2025)
Ireland's cultural and religious identity has transformed considerably in the past three decades. Consequently, the primary school classroom has become an important platform in which to assist young people to develop the tools to interact with an increasingly pluralistic society. However, primary schools in Ireland have frequently been criticised for their response to such changes. In particular, critics have highlighted the mismatch between an increasingly diverse population and the largely denominational primary school system as a major area of concern (Faas, Smith, and Darmody 2018b). Confronted with the recent surge in anti-immigration sentiments and the high incident rates of racism experienced in Ireland, it becomes clear that schools have a critical role to play in terms of social integration and enhancing students cultural and religious literacy during their formative years. This thesis, therefore, examines the response of the Irish primary school sector to the growing cultural and religious diversity in Ireland. It explores key questions related to how the ethos of different Irish primary schools are accommodating diversity and what factors create a dissonance between ethos and practice. In doing so, the study further considers the factors that assist teachers and school leaders to create culturally responsive classroom environments. The study also investigates how the Irish educational system is responding to the diverse educational preferences of parents regarding the types of schools they wish to send their children to. Finally, the study explores how students from diverse cultural and religious backgrounds are exercising their agency to negotiate school belonging. In order to address these questions, this study deployed a multi-method comparative case study design across eight primary schools in Ireland. Overall, the study sampled 97 participants, including students, teachers, school principals and parents. Cases were selected from the four main denominational, multi-denominational and equality-based primary school types in Ireland; Catholic, Church of Ireland (COI), Educate Together (ET) and Community National Schools (CNS). All cases were sampled in both rural and urban locations to examine whether geographical location influenced the delivery of culturally responsive practices. This research provides a timely contribution to knowledge by conducting the first empirical comparative study to examine the complex factors that influence the responsiveness of Irish primary schools to religiously and culturally diverse student populations across four major primary school types in Ireland, and whether these factors vary based on location of the school. In doing so, this thesis offers insights regarding the conditions and factors that allow schools to develop a more culturally responsive school environment and moderate factors that may "other" students from migrant backgrounds. Ireland serves as a useful case study as the social phenomenon that has occurred in the country over the past three decades mirrors that of several European countries in terms of upward migration trends, yet the educational landscape of Ireland remains somewhat unique within the European context. Thus, the importance of this study to discourses on integration and inclusion of diverse groups of students extends beyond Ireland and demonstrates social utility internationally.
APPROVED